Sustainable operations modeling and data analytics - Gunasekaran, Angappa; Subramanian, Nachiappan (Elsevier, 2018)
This editorial introduces the unique attributes of this special issue in the era of climate change, modern slavery, and big data. This special issue envisages the depth of penetration of sustainability, from strategy to the operations level, to understand the extent to which sustainability has attracted researchers and practitioners in dealing with various facets of operations management. Overall, it is encouraging to notice the research developments in all facets of operations management except process type, layout type, forecasting, and queuing. Out of three sustainability dimensions, this special issue received substantial contributions on economic and environmental aspects. All the contributions had at least two sustainability components in their decision models as well as newer analytical solutions. At the end, this piece outlines future research challenges and potential research opportunities.